The master puppeteer - Paterson, Katherine; Wells, Haru. (New York HarperTrophy, 1989)
A thirteen-year-old boy describes the poverty and discontent of eighteenth century Osaka and the world of puppeteers in which he lives.
Reprint. Originally published by HarperCollins, c1975.
Keywords: Puppets -- Fiction; Japan -- Fiction